Seroconversion following COVID-19 vaccination: can we optimize protective response in CD20-treated individuals?. (18th November 2021) - Baker, David; MacDougall, Amy; Kang, Angray S; Schmierer, Klaus; Giovannoni, Gavin; Dobson, Ruth
Abstract: Although there is an ever-increasing number of disease-modifying treatments for relapsing multiple sclerosis (MS), few appear to influence coronavirus disease 2019 (COVID-19) severity. There is concern about the use of anti-CD20-depleting monoclonal antibodies, due to the apparent increased risk of severe disease following severe acute respiratory syndrome corona virus two (SARS-CoV-2) infection and inhibition of protective anti-COVID-19 vaccine responses. These antibodies are given as maintenance infusions/injections and cause persistent depletion of CD20 + B cells, notably memory B-cell populations that may be instrumental in the control of relapsing MS. However, they also continuously deplete immature and mature/naïve B cells that form the precursors for infection-protective antibody responses, thus blunting vaccine responses. Seroconversion and maintained SARS-CoV-2 neutralizing antibody levels provide protection from COVID-19. However, it is evident that poor seroconversion occurs in the majority of individuals following initial and booster COVID-19 vaccinations, based on standard 6 monthly dosing intervals. Seroconversion may be optimized in the anti-CD20-treated population by vaccinating prior to treatment onset or using extended/delayed interval dosing (3–6 month extension to dosing interval) in those established on therapy, with B-cell monitoring until (1–3%) B-cell repopulation occurs prior to vaccination. Some people will take more than a year to replete and therefore protection may depend on either the vaccine-induced T-cell responses that typically occur or may require prophylactic, or rapid post-infection therapeutic, antibody or small-molecule antiviral treatment to optimize protection against COVID-19. Further studies are warranted to demonstrate the safety and efficacy of such approaches and whether or not immunity wanes prematurely as has been observed in the other populations. Abstract : We review emerging evidence indicating that differential rates of B-cell subset repopulation following CD20-depleting antibody treatments can be exploited, to maintain control of autoimmunity whilst allowing SARS-CoV-2 vaccination-induced seroconversion. Extended-interval antibody dosing, supported by use of antiviral antibodies or small molecules may help optimize protection against severe COVID-19. Graphical Abstract: